Unpressurized light aviation aircrafts flight and psysiological data acquisition system - Marques, André Emanuel Castro (2014)
Special thanks to FCT (Fundação para a Ciência e Tecnologia) for the MSc Grant under AIRDEV (Business Models for Airport Development and Management) Project in partnership with MIT – Portugal Program (Reference: MIT- PT-TSAAs/0046/2008). Special thanks to Nonin Medical Inc. for supporting this work with the cerebral oximetry equipment. Special thanks to the OMNI Aviation Training Center for the assistance and availability for flight tests. Special thanks to the Portuguese Air Force for the authorization to conduct Hypobaric Chamber tests in the Aeronautical Medical Center. Special thanks to the Department of Sport Sciences of the University of Beira Interior for the Garmin Forerunner 305. Special thanks to the Department of Informatics of the University of Beira Interior and to the Informatics Engineering Department of the Superior School of Technology of the Polytechnics Institute of Tomar for the assembly of the Atmospheric Sensors Board and the creation of specific software.